Influence of fertilizers on the productivity of potato tubers in the conditions of the Right-Bank Forest-Steppe of Ukraine - М’ялковський, Р. О. (Scientific Progress & Innovations, 2017)
The influence of fertilizers on the productivity of potato tubers in the conditions of the Right-Bank Forest-Steppe of Ukraine was investigated. It was established that the highest mass of tubers was obtained from the combined introduction of organic and mineral fertilizers with the norm of background + N120P120K120 in the middle-grade varieties – 616 g. The high yield of potato tubers was characterized by medium-grade varieties (Vera, Slovianka, Nadiina), while the highest yield was set in the variant (background + N120P120K120) – 38.8 t/ha. Biochemical analysis revealed that the content of starch in potato tubers depended on the variety and background of nutrition, with the highest rate of 17.2 % in the version (without fertilizers).